2012
DOI: 10.2166/wst.2012.858
|View full text |Cite
|
Sign up to set email alerts
|

Impediments and constraints in the uptake of water sensitive urban design measures in greenfield and infill developments

Abstract: Water sensitive urban developments are designed with integrated urban water management concepts and water sensitive urban design measures. The initiatives that may be included are the substitution of imported drinking water with alternative sources using a fit-for-purpose approach and structural and non-structural measures for the source control of stormwater. A water sensitive approach to urban development can help in achieving sustainability objectives by minimising disturbance to ecological and hydrological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 26 publications
(27 reference statements)
0
29
0
Order By: Relevance
“…Research attention has been devoted to understanding the drivers and barriers to adoption of decentralised systems within the broad sustainable urban water management (SUWM) paradigm (Brown and Farrelly, 2009;Naylor et al, 2012;Sharma et al, 2012). This research parallels studies on adoption of distributed energy options (e.g., Allen et al, 2008) and microgrids (e.g., Soshinskaya et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Research attention has been devoted to understanding the drivers and barriers to adoption of decentralised systems within the broad sustainable urban water management (SUWM) paradigm (Brown and Farrelly, 2009;Naylor et al, 2012;Sharma et al, 2012). This research parallels studies on adoption of distributed energy options (e.g., Allen et al, 2008) and microgrids (e.g., Soshinskaya et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Increased concentration of contaminants in wastewater has been known to cause sewer problems, such as sewer blockage, odor and corrosion [35]. Therefore, whilst the investment in decentralized water system technologies can be warranted for developments in growth areas of cities, assessing the impacts of decentralized systems on the existing developments remains challenging due to the lack of understanding of the interaction between decentralized and centralized systems [35,36]. Further adoption of the decentralized systems has thus far been limited to demonstration projects [37].…”
Section: Decentralized Water Supply Systemsmentioning
confidence: 99%
“…On the other hand, such transition of traditional urban water system to hybrid water supply systems have significant effects on central networks [13], particularly the sewage network and storm water drains. The use of decentralized water supply options changes both the wastewater and stormwater flow regimes and contaminants' composition [36,93,98]. Thus it can be argued that while these hybrid water supply systems seem to be promising, there are some inherent challenges such as public acceptance, particularly for new technologies and unfamiliar practices (e.g., greywater recycling), unknown impacts, understanding the interaction between centralized and decentralized services and diverse infrastructure management.…”
Section: Hybrid Water Supply Systemsmentioning
confidence: 99%
“…Such a definition and drivers for decentralised systems also aligns to the WSUD philosophy. Sharma et al [6] also highlighted the key impediments to greater WSUD uptake including inadequacy and fragmentation of current governance, regulation and guidelines for WSUD; lack of skills and knowledge; potential for increased public health risk; and, poor financial incentives. Similarly, Sapkota et al [7] has identified gaps in knowledge for the interactions between centralised conventional and alternative systems.…”
Section: Introductionmentioning
confidence: 99%